Extreme active matter at high densities - Rituparno Mandal (Nature Portfolio, 2020)
While active matter exhibits unusual dynamics at low density, high density behavior has not been explored. Mandal et al. show that extreme dense active matter, shows a rich spectrum of behaviour from intermittent plastic bursts and turbulence, to glassy states and jamming in the limit of infinite persistence time.